Handling Missing Data in Bivariate Gamma Generation Data Using the Random Forest Method - Muhammad Arib Alwansyah Arib; Ramya Rachmawati Ramya (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2025)
Missing data is a common problem in data analysis that can reduce the quality and accuracy of study results if not handled properly. This study aims to evaluate the performance of the Random Forest (RF) imputation method at various levels of missing value proportions, namely 5%, 10%, 15%, and 20%. The data used are Bivariate Gamma data of 200 observations with two variables, generated using RStudio software. Evaluation of imputation performance is carried out by considering the correlation value between the imputed data and the original data, the p-value as an indicator of the significance of the difference, and the error measures Mean Absolute Percentage Error (MAPE) and Root Mean Square Error (RMSE).